Factors influencing institutional repositories in some Universities in Nigeria (2017)
Establishment, development and sustenance of institutional repository has been a challenging task for many institutions of higher learning in Nigeria while many other institutions across the globe have effectively managed issues of institutional repository in their institutions. Although, studies has be conducted on institutional repository in Nigerian Universities but such studies are yet to identify factors that influence institutional repositories in the country. Therefore, the study assessed factors influencing institutional repository in some universities in Nigeria. The study adopted the descriptive survey research design using a self-developed structured questionnaire. A multistage sampling procedure was employed to sample 751 staff (436 males and 315 females) of universities in Nigeria. Two research questions were raised. Data generated were analysed using descriptive statistics. The finding revealed that the development and sustenance of institutional repositories in university libraries in Nigeria have been very slow and quite uneven, due to the numerous institutional and external factors affecting the sustenance of institutional repositories. Based on the findings, some recommendations were made